Asset price shocks and inflation in the Finnish economy - Tero Koivisto (Bank of Finland, 2024)
This study aims to explore the extent to which changes in wealth contributes to inflation utilizing a highly flexible non-Gaussian SVAR framework which minimizes the risk of distributional misspecification. We employ narrative sign restrictions to label the asset price shock and leverage the property of the Bayesian approach to compute the posterior probability of each shock satisfying these proposed restrictions. The structural shock associated with wealth has a positive impact on private consumption and GDP. The asset price shock is also positively related on consumer prices. Therefore, variations in wealth appear to stimulate the real economy.
urn:nbn:fi-fe2024061955575
Keywords: E31; E44; 330; Asset price shocks; wealth effect; inflation; structural vector autoregression; non-Gaussianity